Carrot or stick? A study on “bid-rigging norms” by simulation: inducing factors and deterring measures - Morofuji, Hideyuki; Kurahashi, Setsuya (Frontiers in Applied Mathematics and Statistics, 2023)
This study aims to analyze the structure of the emergence and maintenance of the cartel mechanism as an informal organization and the measures to deter bid-rigging. We propose an agent-based bid-rigging norms model and validate it with a mathematical model. We clarify that the auction system primarily used in public procurements has a structure inducing bid-rigging in which meta-norms are unnecessary. We also show that punishment for deviation from bid-rigging plays a critical role in establishing and maintaining it. In addition, we explore the authorities' actions to deter bid-rigging by examining three measures: the flexible setting of reserve prices, the administrative surcharge and leniency system under the Antimonopoly Law, and applying the bid-rigging offense under the Criminal Law. As a result, the study reveals that the administrative surcharge and the leniency system are insufficient to deter bid-rigging, and the adequate measures are the flexible setting of reserve prices and applying the bid-rigging offense. Furthermore, the simultaneous implementation of these three measures more effectively enables deterring bid-rigging.